Complex housing causes a robust increase in dendritic complexity and spine density of medial prefrontal cortical neurons - Ashokan, Archana (2018)
Prelimbic cortex and infralimbic cortex, parts of the ventromedial prefrontal cortex, are critical brain regions for generating a flexible behavioral response to changing environmental contingencies. This includes the role of these brain structures in the extinction of learned fear, decision making and retrieval of remote memories. Dendritic structure of medial prefrontal cortex neurons retains significant structural plasticity in adulthood. This has been mainly demonstrated as dendritic atrophy and loss of dendritic spines due to chronic stress. It remains unknown if housing condition of the animals itself can cause opposing changes in the dendritic organization. In that backdrop, here we report that short-term increase in complexity of the housing causes a robust increase in complexity of dendritic architecture of prelimbic and infralimbic neurons. This is reflected in the dendritic expansion of prelimbic neurons and increase in spine density of prelimbic and infralimbic neurons. These results suggest that non-invasive changes in the housing environment can be harnessed to study brain reserves for the flexible and species-typical behaviors.